Quality assuring "Plan of the day" selection in a multicentre adaptive bladder trial: Implementation of a pre-accrual IGRT guidance and assessment module. (November 2019) - Patel, Emma; Tsang, Yat; Baker, Angela; Callender, Jenny; Hafeez, Shaista; Hall, Emma; Hansen, Vibeke Nordmark; Lewis, Rebecca; McNair, Helen; Miles, Elizabeth; Huddart, Robert
Highlights: A multi-centre trial QA programme including adaptive RT plan selection was developed. This novel trial QA approach has been validated by 71 RTTs from 10 UK centres. This process increased RTTs' confidence; resulted in appropriate on-trial adaptive RT plan selection. Abstract: Background and purpose: Hypofractionated bladder RT with or without image guided adaptive planning (HYBRID) is a multicentre clinical trial investigating "Plan of the Day" (PoD) adaptive radiotherapy for bladder cancer. To ensure correct PoD selection a pre-accrual guidance and assessment module was developed as part of an image guided radiotherapy quality assurance (IGRT QA) credentialing programme. This study aimed to evaluate its feasibility and effectiveness across multiple recruiting centres. Materials and methods: Individuals from participating centres remotely accessed an image database in order to complete the PoD module. An assessment score of ≥83% was required in order to receive QA approval. A questionnaire was used to gather user feedback on the module. PoD decisions for the first patient at each recruiting centre were retrospectively reviewed for protocol adherence. Results: 71 radiation therapists (RTTs) from 10 centres completed the PoD module. The median assessment score was 92% (Range: 58–100%) with 79% of RTTs passing the assessment on first attempt. All questionnaire respondents reported that the PoD module prepared them for plan selection. In 51/60 of on-trial treatments reviewed, the PoD selected by the centre agreed with QA reviewers. Conclusions: The PoD QA module was successfully implemented in a multicentre trial and enabled pre-accrual assessment of protocol understanding. This increased operator confidence and resulted in appropriate PoD selection on-trial.